CT Findings of Patients Treated with Irreversible Electroporation for Locally Advanced Pancreatic Cancer. (5th November 2015) - Akinwande, Olaguoke; Ahmad, Shakeeb S.; Van Meter, Tracy; Schulz, Brittany; Martin, Robert C. G.
Abstract : Introduction . In patients with locally advanced pancreatic cancer (LAPC), IRE has been shown to be safe for local disease control and palliation. As IRE continues to gain acceptance it is important to characterize the expected imaging findings. Materials and Methods . A review of our prospective soft tissue ablation registry from July 2010 to June 2013 was performed on patients who had undergone IRE for LAPC. Five masses treated with intraoperative IRE ablation for pancreatic tumors that underwent CT imaging before and after ablation were reviewed. Results and Discussion . Following IRE, the postablation bed is larger than the original ablated tumor. This ablation zone may get smaller in size (due to decreased edema and hyperemia) in the following months and more importantly remains stable provided there is no recurrence. In cases of recurrent disease there is increased size of the ablation bed, mass effect, and new or worsening vascular encasement or occlusion. Conclusion . CT imaging remains the best current imaging modality to assess post-IRE ablation changes. Serial imaging over at least 2–6 months must be employed to detect recurrence by comparing with prior studies in conjunction with clinical and serum studies. Larger imaging studies are underway to evaluate a more ideal imaging modality for this unique patient population.